The Effect of Islamic Attributes and Destination Affective Image on the Reputation of the Halal Tourism Destination of Jakarta - WIDJAJA, Yunni Indrani; KHALIFA, Gamal S. A.; ABUELHASSAN, Abuelhassan Elshazly (Journal of Environmental Management and Tourism; Vol 11 No 2 (2020): JEMT Volume Xi Issue 2(42) Spring 2020, 2020)
Tourism industry recognizes the growing interest in Halal tourism from both the perspectives of practitioners and researchers. Indonesia was chosen as the world's best halal tourism destination this year according to the 2019 Global Muslim Travel Index (GMTI) and outperformed 130 destinations from around the world. Among the 10 most favorite halal tourism destinations, Jakarta has the most unique characteristics compared to the other nine provinces. Related to this background, this study aims to examine the effect of Islamic attributes and destination affective image on the reputation of the halal tourism destination of Jakarta. The research design outlines the use of quantitative research approaches. The unit of analysis and observation is International Muslim tourists who visited Jakarta. The Central Statistics Bureau (BPS) recorded the number of foreign visitors arriving DKI Jakarta amounted to 2,313,742 people at 2013. Hair et al. (1992) suggest the minimum sample size for SEM analysis is 100 to 200. So based on this opinion, this study will take a sample of 200, in accordance with the terms of use of SEM (Structural Equation Modeling) as analytic tools to test the hypotheses. The study was conducted in the cross-section period of 2019. The results showed that the Islamic Attributes and Destination Affective Image affect the Destination Reputation. Destination reputation is more dominantly built by destination affective image compared to Islamic attributes. This finding has implications for related stakeholders that the development of destination affective image needs to be prioritized to support Jakarta's destination reputation as one of the halal tourism destinations in Indonesia. It mainly concerns on the aspects of natural and cultural resources, security, night life and entertainment, accessibility, and quality / price ratio.